FACTOR THAT AFFECTING DEBT TO EQUITY RATIO IN THE INDONESIA’S TOURISM INDUSTRY SECTOR - Tan Natasya Yona Calista; Purwanto Purwanto (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
The research aim is to examine the influence of working capital turnover, current ratio, cash ratio, firm size and return on assets toward debt to equity ration in the tourism industry sector listed on the Indonesia Stock Exchange. This is a quantitative research which takes data from the company’s audited financial statement. There are five independent variables which are being examined by descriptive statistical analysis, classical assumption tests, multiple linear regression, and hypotheses testing. The population of this research is tourism companies and stores 10 samples of companies fulfilled certain criteria in the period of 2012-2018 annually. The technique used for multiple linear regression panel data is the random effect model. The outcomes reveal a value of adjusted R-squared towards dependent variable is 33.22% and the independent variables of working capital turnover, current ratio, firm size and return on assets have a significant influence on debt to equity ratio in hypotheses testing. The most significant independent variable influences debt to equity ratio in the tourism industry sector in Indonesia is working capital turnover. High working capital turnover indicates this shortage of working capital which may be due to high inventory turnover, accounts receivable or cash balances that are too small.